ChemInform Abstract: Catalytic ortho‐Acetoxylation of Masked Benzyl Alcohols via an Exo‐Directing Mode. Issue 41 (October 2015) - Ren, Zhi; Schulz, Jonathan E.; Dong, Guangbin
Abstract 2, 6‐Dimethoxybenzaldoxime is found to be a highly efficient directing group for the ortho‐acetoxylation of various masked primary and secondary benzyl alcohols.